Avaliação da implantação e dos resultados do subprograma Gestão por Bacias, Programa Cultivando Água Boa (Itaipu) na sub-bacia hidrográfica Santa Rosa - município de Cascavel (PR) - Silva, Silvana Severino da (2017)
It was started, in 2003, a socio-environmental activity named "Cultivating Good Water Program" (ITAIPU) on the border of Brazil and Paraguay. It is formed of 20 subprograms, including The Watershed Management Subprogram. The research issue is the importance of knowing the subprogram implantation and results until 2015, in Paraná III watershed. The general objective of the study is to analyze the Itaipu Binacional watershed management subprogram implantation and the results for environment protection actions in Santa Rosa watershed, municipality of Cascavel, in Brazil. Only one municipality and one watershed that are part of Cultivating Good Water, were used for delimitation of this study. Considering Paraná watershed III management area, we selected Santa Rosa watershed in Novo Horizonte line, rural area municipality of Cascavel, Paraná. We present general and specific data related to documents, worksheets, maps and images. Thus, we know how was the participation of the central and municipal managers and rural producers in the watershed management during the period from 2003 to 2015. Along the management watershed study we performed field research with rural producers and identified that the implemented actions by the Cultivating Good Water Itaipu contributed to preservation of local watersheds. Some of the benefits to rural properties are the following actions: improving and gravelling roads, riparian vegetation and sources protection. All the surveyed rural producers said the improving and gravelling road are priority.